Insights into the Influences of Carboxymethyl-β-Cyclodextrin on DNA Formulations Characteristics and Gene Transfection Efficiency - Elsana, Hassan; Mysina, Svetlana; Elkordy, Eman A.; Carr-wilkinson, Jane; Elkordy, Amal Ali (Current Drug Delivery, 2018)
Background: Gene therapy is an expanding field and it can treat genetic and acquired diseases. Objective: It was found that formulations with DNA: CM-β–CD (Carboxymethyl-beta-cyclodextrin): Pluronic-F127 1:3:3 and 1:3 DNA: CM-β–CD are the most stable formulations indicating high incorporation of DNA within CM-β –CD. Method: Gel electrophoresis revealed DNA with low CM-β –CD concentration has formed a more stable complex. Samples 1:3 DNA: CM-β–CD and 1:3:3 DNA: CM-β–CD: Pluronic-127 show no DNA fragment, suggesting good condensation of DNA inside cyclodextrin cavity. Results: This was confirmed by fluorescence data where fluorescence intensity was reduced for samples DNA: CM-β–CD 1:3. Overall, the findings showed that Carboxymethyl-beta-cyclodextrin (as a novel non-viral gene vector) was able to provide condensation and protection to the DNA, with and without Pluronic-F127, at low concentration. Conclusion: pDNA/CM-β–CD complex has not only shown to be able to transfect COS 7 and SHSY5Y cell lines, but it gives a higher transfection efficiency than that produced by the TransIT-LT1 commercial transfection reagent.
Keywords: transfection